Longitudinal assessment of amyloid-beta deposition in initially amyloid-negative non-demented individuals with [11C]-PIB PET imaging. Issue 35 (3rd September 2021) - Hatashita, Shizuo; Wakebe, Daichi
Abstract : Abstract: This study aimed to assess the longitudinal changes in amyloid beta (Aβ) deposition in cortical regions with [11C]-PIB PET in initially amyloid-negative non-demented subjects and evaluate whether amyloid-negative subjects convert to amyloid-positive. Sixteen cognitively normal (CN) and 7 mild cognitive impairment (MCI) subjects (aged 60–75 years), who were amyloid-negative at baseline, underwent 60-minute dynamic [11C]-PIB PET and cognitive assessment over 5.0 to 9.4 years of a long follow-up, and the apolipoprotein-E (APOE) genotype was assessed. Regions of interest were defined in the bilateral cortex on coregistered MRI. Quantitative analysis of [11C]-PIB was performed using the distribution value ratio (DVR). Longitudinal changes in global and regional PIB DVRs were evaluated in the same regions, and the annual rate of change in the PIB DVR was calculated. Seven (30.4%) of 23 initially amyloid-negative non-demented subjects converted to globally amyloid-positive (global PIB DVR ≥1.40) over a follow-up of 6.5 ± 1.4 years (converter). The global PIB DVR in converters increased from 1.22 ± 0.07 at baseline to 1.63 ± 0.15 (n = 7, P < .01) at last follow-up, and an annual increase of global PIB DVR was 0.057 ± 0.019/year (n = 7, P < .01). In contrast, the global PIB DVR in the remaining 16 subjects was 1.15 ± 0.07 at baseline and did not change over a follow-up period (stable). The APOE ε4 allele was present in 4 (57.1%) of the 7 converters, differing from 2 (12.5%) of 16 stable subjects (Fisher's exact test, P < .05). Three amyloid-negative MCI subjects had an annual increase in global PIB DVR above 0.061/year and became positive at 2.8 ± 0.5 years of follow-up, which was faster than 5.0 ± 2.0 years in 4 CN subjects. The regional PIB DVR that increased early above the regional positivity threshold was most frequently found in the right lateral temporal cortex (71.4%), followed by the left frontal cortex (41.8%). Our results suggest that the initially amyloid-negative CN and MCI subjects, especially with APOE ε4, can become globally amyloid-positive over a longer time, based on early regional Aβ deposition in the lateral temporal cortex and/or frontal cortex.